Earth in the balance: Forging a new common purpose - Gore, AL. (New Delhi : Viva Books Private Limited, 1993)
Cover; Half Title; Title Page; Copyright Page; Dedication; Table of Contents; Foreword: The Coming "Environment Decade"; Introduction; Part I - Balance at Risk; 1. Ships in the Desert; 2. The Shadow Our Future Throws; 3. Climate and Civilization: A Short History; 4. Buddha's Breath; 5. If the Well Goes Dry; 6. Skin Deep; 7. Seeds of Privation; 8. The Wasteland; Part II - The Search for Balance; 9. Self-Stewardship
Includes bibliography and index.
Keywords: Environmental protection; Environmental technology; Human ecology; Social biology. -- .